2008
DOI: 10.1136/jcp.2008.060004
|View full text |Cite
|
Sign up to set email alerts
|

Higher expression of deoxyuridine triphosphatase (dUTPase) may predict the metastasis potential of colorectal cancer

Abstract: Aims: 5-Fluorouracil (5-FU) is one of the most widely used anticancer drugs; however, the activity of 5-FU is determined by the presence of several enzymes that limit its activation or degradation, and these include dihydropyrimidine dehydrogenase (DPD), orotate phosphoribosyl transferase (OPRT), thymidylate synthase (TS), thymidine kinase (TK), thymidine phosphorylase (TP) and deoxyuridine triphosphatase (dUTPase). The aim of this study was to compare the expression levels of these enzymes between the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 11 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…Nevertheless, the expression levels of UNG showed little effect on sensitivity to TS inhibitors (17,18); therefore, it has been suggested that dUTPase plays a primary role in the mechanism against misincorporation of 5-FU and uracil. A significant increase in dUTPase expression is observed in various cancers, and it has been suggested that higher expression leads to resistance to 5-FUbased chemotherapy (13,16,(19)(20)(21)(22). The critical role of dUTPase in 5-FU and uracil misincorporation-mediated cytotoxicity makes it a potential target for cancer treatments by combining a dUTPase inhibitor with a TS inhibitor (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the expression levels of UNG showed little effect on sensitivity to TS inhibitors (17,18); therefore, it has been suggested that dUTPase plays a primary role in the mechanism against misincorporation of 5-FU and uracil. A significant increase in dUTPase expression is observed in various cancers, and it has been suggested that higher expression leads to resistance to 5-FUbased chemotherapy (13,16,(19)(20)(21)(22). The critical role of dUTPase in 5-FU and uracil misincorporation-mediated cytotoxicity makes it a potential target for cancer treatments by combining a dUTPase inhibitor with a TS inhibitor (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila melanogaster, the expression of dUTPase was shown to be under developmental control [5,10]. In cancer tissues, overexpression of the nuclear isoform of dUTPase was associated with poor prognosis [11][12][13].…”
mentioning
confidence: 99%
“…It is suggested that dUTPase may be a predictive biomarker for the metastatic potential of colorectal cancer. [24]. Further evaluations must confirm these data.…”
Section: Deoxyuridine Triphosphate Nucleotidohydrolase (Dutpase)mentioning
confidence: 66%